Electrophysiological Evaluation of People With Volatile Substance Addiction - Nurten Uzun; Yılmaz Kendirli; Ayşegül Gündüz; Gülçin Benbir (Türk Nöroloji Dergisi, 2008)
OBJECTIVE: Scientific BACKGROUND: There is an increase in addiction of volatile substances in recent years. Miscellaneous electrophysiological pathological findings are determined in volatile substance abusers. OBJECTIVE: In this study, we aim to examine the neurologic effects of these substances by electrophysiologic methods.